The use of discourse markers in conversation: The case of “myślę” – “I think” in Polish Career Clean Coaching - Juszczyk, Konrad; Konat, Barbara (Lingua Posnaniensis, 2024)
People find it difficult to talk about abstract concepts such as their future career plans. The discourse marker “I think” is used to express uncertainty and soften the force of a proposition. The objective of this paper is to demonstrate how specific context and bounded topic of conversation influence the use of the discourse marker “I think” in Polish (myślę) as a structuring discourse marker. A total of 23 participants were recorded during Career Clean Coaching sessions and the usage of “I think” in the resulting corpus was compared to other Polish conversational corpora. The qualitative study of the semantics of “I think” indicates that this discourse marker serves a hedging function. The quantitative analysis of the frequency of the discourse marker “I think” in Polish conversational corpora and in the Career Clean Coaching corpus reveals significant differences. The results indicate that pragmatic factors, namely the topic, context and protocol of the conversation, exert a strong influence on the usage of “I think”.